TGF-β1 Suppresses T Cell Infiltration and VP2 Puff B Mutation Enhances Apoptosis in Acute Polioencephalitis Induced by Theiler’s Virus - Tsunoda, Ikuo (2007)
GDVII and DA strains of Theiler’s murine encephalomyelitis virus (TMEV) differ in VP2 puff B. One week after GDVII virus infection, SJL/J mice had large numbers of TUNEL(+) apoptotic cells with a relative lack of T cell infiltration in the brain. DA viruses with mutation in puff B induced higher levels of apoptosis than wild-type DA virus, but levels of inflammation in brains were similar between DA and DA virus mutants. The difference in inflammation among TMEVs could be due to TGF-β1 expression that was seen only in GDVII virus infection and negatively correlated with CD3(+) T cell infiltration.